Unmet health care need and income-related horizontal equity in access during the COVID-19 pandemic - Apostolos Davillas; Andrew M. Jones (University of Essex, Institute for Social and Economic Research (ISER), 2020)
Using monthly data from the Understanding Society (UKHLS) COVID-19 Survey we analyse the evolution of unmet need and assess how the UK health care system performed against the norm of horizontal equity in health care access during the first wave of COVID-19 wave. Unmet need was most evident for hospital care, and less pronounced for primary health services (medical helplines, GP consultations, local pharmacist advice, over the counter medications and prescriptions). Despite this, there is no evidence that horizontal equity, with respect to income, was violated for NHS hospital outpatient and inpatient care during the first wave of the pandemic. There is evidence of pro-rich inequities in access to GP consultations, prescriptions and medical helplines at the peak of the first wave, but these were eliminated as the pandemic progressed. There are persistent pro-rich inequities for services that relate to individuals' ability to pay (over the counter medications and advice from the local pharmacist).
Keywords: C1; D63; I14; 330; inequity; COVID-19; unmet need; health care; UKHLS